High-performance magnetorheological fluid and preparation process thereof

By adopting the combination of ternary composite magnetic particles, two-component surface modifiers and conductive composite materials, the shortcomings in the existing magnetorheological fluids in magnetic response performance, stability and shear stress adjustment capabilities are solved, and efficient magnetorheological performance and long-term stability are achieved.

CN119724810APending Publication Date: 2025-03-28LUOYANG INST OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411883123.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing magnetorheological fluids have shortcomings in magnetic response performance, particle dispersion, stability and shear stress adjustment capabilities, which are difficult to meet the needs of complex working conditions.

Method used

The magnetic particles are mixed in a ratio of 1:1:1 and synthesized by hydrothermal or solvothermal method. The two-component surface modifier of polyvinyl alcohol and polyethyleneimine is optimized to optimize the combination of base liquid and stabilizer, and carbon nanotubes or graphene are added to form a conductive composite material.

Benefits of technology

It significantly improves the magnetic response sensitivity and particle stability of magnetorheological fluid, expands the range of shear stress adjustment, enhances the anti-settlement and shear resistance, and meets the efficient performance under complex working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724810A_ABST
    Figure CN119724810A_ABST
Patent Text Reader

Abstract

The invention relates to the field of magnetorheological fluid materials, and discloses a high-performance magnetorheological fluid which comprises 40%-60% of magnetic particles, 1%-10% of a surface modifier, 60%-90% of a base fluid and 0.5%-5% of a stabilizer. Ferrite, cobalt ferrite and nickel ferrite are mixed according to the proportion of 1: 1: 1 to form magnetic particles, the magnetic particles are synthesized through a hydrothermal method or a solvothermal method, the particle size of the particles is strictly controlled to be 10-50 nm, and the characteristics of high magnetism, low aggregation and uniform particle size distribution are achieved. According to the technical scheme, the magnetic response sensitivity of the magnetorheological fluid is remarkably improved, the shear stress adjusting range is expanded to 2Pa-500Pa, the stable rheological property under different working conditions is ensured, the magnetorheological fluid can realize dynamic adjustment of the shear stress range of 2Pa-500Pa under the action of a 0.1 T-1. 0T magnetic field, the magnetic response time is less than 5 seconds, and the stability of the magnetorheological fluid is improved. The stability and the rheological property are excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetorheological fluid materials, in particular to a high-performance magnetorheological fluid and a preparation process thereof. Background Art

[0002] Magnetorheological fluid is a functional smart material whose core characteristic is that the viscosity of the fluid can change rapidly and reversibly under the action of an external magnetic field. This material has a wide range of applications in shock absorbers, clutches, actuators and precision control equipment. However, the magnetorheological fluid in the prior art has many deficiencies in performance and stability, which limits its further promotion and application.

[0003] In the composition of magnetorheological fluid, magnetic particles are its key functional components, which directly affect its magnetic response performance, shear stress adjustment range and anti-sedimentation stability. The existing technology usually uses a single magnetic material (such as Fe3O4) as the particle source, but due to the single type of magnetic material, weak magnetic response performance, and uneven particle size distribution, the performance of magnetorheological fluid is difficult to meet the requirements of complex working conditions. In addition, the particles are easy to aggregate and settle in the base liquid, which seriously affects its stability in long-term use.

[0004] In order to improve the dispersibility of magnetic particles in the base fluid, the existing technology usually modifies the particles through surface modifiers. However, traditional surface modification technologies mostly use a single modifier, such as polyvinyl alcohol (PVA) or fatty acids, which have a single function and are difficult to provide long-term and effective particle stability under complex environmental conditions (such as high shear, high temperature or long-term standing), resulting in poor applicability of magnetorheological fluids.

[0005] In addition, magnetic response speed is one of the important indicators of magnetorheological fluid performance. The magnetic particles in the prior art usually lack the synergistic effect with the conductive composite material, resulting in a long magnetic response time of the magnetorheological fluid and the inability to quickly adjust the viscosity. This limitation in response speed seriously affects the application of magnetorheological fluid in high-dynamic control equipment. At the same time, due to the unreasonable design of the particle system, the shear stress adjustment range of the existing magnetorheological fluid is relatively narrow and cannot meet the high-precision control requirements of multiple working conditions.

[0006] Finally, the design of the stabilization system in the prior art is insufficient. The combination of a single base liquid (such as mineral oil or water-based liquid) and a single surfactant can easily lead to magnetic particle sedimentation or stratification under high temperature, high shear or long-term static conditions, and the rheological properties of the magnetorheological fluid decay quickly and the service life is short, which limits its further application in the fields of industry, aerospace, etc.

[0007] Therefore, the present invention proposes a high-performance magnetorheological fluid and a preparation process thereof to solve the deficiencies of the prior art. Summary of the invention

[0008] In view of the deficiencies of the magnetorheological fluid in the prior art in terms of magnetic response performance, particle dispersion, stability and shear stress regulation ability, the present invention provides a high-performance magnetorheological fluid and its preparation process. By optimizing the material composition, surface modification, composite material design and stabilization system of magnetic particles, the present invention achieves high-efficiency performance of the magnetorheological fluid under complex working conditions and solves many technical problems in the prior art.

[0009] To achieve the above objectives, the present invention is implemented by the following technical solutions: A high-performance magnetorheological fluid, comprising the following raw materials in percentage by mass:

[0010] Magnetic particles: 40%-60%, the magnetic particles are composed of ferrite, cobalt ferrite, nickel ferrite or their alloys, the composition ratio of ferrite, cobalt ferrite and nickel ferrite is 1:1:1, and the particle size ranges from 10 to 100 nm;

[0011] Ferrite (Fe3O4) has excellent magnetic properties and stability;

[0012] Cobalt ferrite (CoFe2O4) provides higher coercivity and magnetic anisotropy;

[0013] Nickel ferrite (NiFe2O4) has low electrical conductivity and reduces eddy current losses.

[0014] The ternary composite system combines the advantages of each, improving the magnetic response sensitivity and particle stability. Particle size control between 10-100nm helps reduce particle sedimentation rate and enhance the shear performance of magnetorheological fluid.

[0015] Significantly improve the magnetic response performance of magnetorheological fluid, so that the shear stress variation range reaches 2Pa to 500Pa under 0.1T-1.0T magnetic field;

[0016] The particle size is evenly distributed, which effectively reduces the sedimentation rate and improves the dispersion stability;

[0017] The optimized ternary composite particles overcome the limitations of the existing technology of insufficient performance of a single material.

[0018] Surface modifier: 1%-10%, the surface modifier is polyvinyl alcohol, polyethyleneimine, polyacrylic acid or a combination thereof, the mass concentration of the polyvinyl alcohol is 10%-20%, and the mass concentration of the polyethyleneimine is 5%-10%;

[0019] Base fluid: 60%-90%, the base fluid is mineral oil, water-based liquid, synthetic oil or a mixture thereof;

[0020] Stabilizer: 0.5%-5%, the stabilizer is a surfactant, used to prevent the aggregation and sedimentation of magnetic particles, the surfactant is sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone or a combination thereof.

[0021] SDBS is a surfactant that effectively inhibits aggregation by reducing the surface energy between particles;

[0022] PVP forms an adsorption layer to increase the stability of particles in the base liquid.

[0023] Preferably, the synthesis method of the magnetic particles is a hydrothermal method or a solvothermal method, the reaction temperature is controlled at 120°C to 200°C, the reaction time is 2 hours to 12 hours, the precursor concentration is 0.1 mol / L to 1 mol / L, and the particle size of the magnetic particles is controlled between 10nm-50nm.

[0024] The hydrothermal and solvothermal methods can precisely control the morphology and size of the particles and prepare uniform nanoparticles;

[0025] Controlling the reaction conditions (temperature, time, precursor concentration) can significantly optimize the magnetic properties of the particles.

[0026] Highly magnetic and low-agglomeration nanoparticles significantly improve magnetic response sensitivity;

[0027] The problem of wide particle size distribution and uneven performance in the prior art is overcome.

[0028] Preferably, the surface modifier is a combination of polyvinyl alcohol and polyethyleneimine, wherein the mass concentration of polyvinyl alcohol is 10%-20%, the mass concentration of polyethyleneimine is 5%-10%, and the total mass concentration of the surface modifiers is 5%-15%.

[0029] PVA has strong hydrophobicity and good film-forming properties, which increases the compatibility between particles and base liquid;

[0030] PE I provides a strong charge effect, improving the electrostatic stability of the particles;

[0031] The synergistic effect of the two components forms a steric hindrance and a charge barrier, effectively preventing particle aggregation and sedimentation. The dispersion stability is significantly improved, and there is no obvious sedimentation after standing for 12 months.

[0032] The particle size distribution is uniform, which improves the long-term service life of the magnetorheological fluid;

[0033] The problem of poor dispersion effect and particle agglomeration of a single modifier in the prior art is overcome.

[0034] Preferably, the base liquid is mineral oil, water-based liquid, synthetic oil or a mixture thereof, the water-based liquid is deionized water, alcohol solution or saline solution, and the surfactant is sodium dodecylbenzene sulfonate or polyvinyl pyrrolidone.

[0035] Mineral oil provides good lubricity and viscosity;

[0036] Water-based liquids enhance thermal conductivity and reduce operating temperatures;

[0037] Synthetic oil has excellent stability in high temperature environment. The mixed base fluid system combines the advantages of each base fluid and optimizes viscosity and thermal stability.

[0038] Improve the high and low temperature adaptability of magnetorheological fluid, and make it applicable in a wider temperature range;

[0039] Maintain stable rheological properties under high shear and dynamic operating environments;

[0040] The mixed base liquid system effectively solves the problem of poor stability of a single base liquid in the prior art.

[0041] Preferably, the surface of the magnetic particles is coated with a ceramic material, and the ceramic material is SiO2 or TiO2, and the coating ratio is 2%-5%.

[0042] SiO2 or TiO2 coating forms a protective shell to reduce direct contact and agglomeration between particles;

[0043] The coating enhances the corrosion resistance and chemical stability of the particles.

[0044] Improve the chemical resistance of magnetorheological fluid to adapt to complex working conditions;

[0045] The performance is stable during long-term use without significant attenuation;

[0046] The problem of easy oxidation of particle surface and unstable rheological properties in the prior art is overcome.

[0047] Preferably, the magnetic particles are compounded with an electrically conductive composite material, the electrically conductive composite material is carbon nanotubes or graphene, and the compounding ratio is 5%-10%.

[0048] The magnetic particles are compounded with carbon nanotubes (CNTs) or graphene, and the compounding ratio is 5%-10%.

[0049] Carbon-based materials enhance electrical conductivity, form electromagnetic synergy, and improve magnetic response performance;

[0050] The two-dimensional structure of graphene improves particle dispersibility.

[0051] The magnetic response time is shortened to less than 5 seconds, and the dynamic response performance is greatly improved;

[0052] The shear stress adjustment range is extended to 10Pa-500Pa;

[0053] The invention solves the problems of slow magnetic response speed and narrow dynamic adjustment range in the prior art.

[0054] Preferably, a process for preparing a high-performance magnetorheological fluid comprises the following steps:

[0055] (1) synthesizing magnetic particles, wherein the magnetic particles are composed of ferrite, cobalt ferrite or nickel ferrite, synthesized by a hydrothermal method or a solvothermal method, and the particle size is controlled between 10 nm and 50 nm;

[0056] (2) surface modification treatment, coating the surface of the magnetic particles, wherein the coating material is polyvinyl alcohol or polyethyleneimine, and the mass concentration of the surface modifier is 1%-10%;

[0057] (3) preparing a base liquid, selecting mineral oil as the base liquid, and adding a stabilizer, wherein the stabilizer is a surfactant, and the concentration of the surfactant is 0.5%-5%;

[0058] (4) Mixing preparation: adding the surface-modified magnetic particles into the base liquid, and uniformly dispersing them by high-speed stirring or ultrasonic dispersion technology to obtain a magnetorheological fluid.

[0059] Preferably, the magnetorheological fluid is used to adjust the shear stress within a magnetic field strength range of 0.1T to 1.0T, and the shear stress varies within a range of 2Pa to 500Pa.

[0060] Preferably, the magnetic response time of the magnetorheological fluid is less than 30 seconds, and the viscosity adjustment ability under the action of the magnetic field reaches the maximum response value within 2 seconds.

[0061] The present invention provides a high-performance magnetorheological fluid and a preparation process thereof. It has the following beneficial effects:

[0062] 1. The present invention uses ferrite, cobalt ferrite and nickel ferrite in a 1:1:1 ratio to form magnetic particles, synthesized by hydrothermal or solvothermal methods, and strictly controls the particle size between 10-50nm, achieving the characteristics of high magnetism, low aggregation and uniform particle size distribution. This technical solution significantly improves the magnetic response sensitivity of the magnetorheological fluid, expands the shear stress adjustment range to 2Pa-500Pa, and ensures stable rheological properties under different working conditions. Compared with the insufficient magnetic response performance of a single magnetic material in the prior art, and the performance instability caused by a wide particle size control range, the present invention solves the technical bottleneck of insufficient magnetic particle performance and a narrow shear stress adjustment range.

[0063] 2. The present invention combines polyvinyl alcohol (PVA) and polyethyleneimine (PEI) as surface modifiers, and optimizes the surface properties of magnetic particles through dual surface modification technology, wherein the mass concentration of PVA is 10%-20%, and the mass concentration of PEI is 5%-10%. This solution effectively enhances the compatibility of particles with the base liquid, reduces particle agglomeration, and significantly improves the dispersibility and anti-sedimentation properties of the magnetorheological fluid through the dual effects of electrostatic repulsion and steric hindrance, so that it can still maintain stable performance under long-term standing and high shear conditions. Compared with the problem in the prior art that a single modifier is easily restricted by environmental conditions and causes particle sedimentation, the present invention effectively solves the technical shortcomings of insufficient stability of magnetorheological fluids and easy aggregation of particles.

[0064] 3. The present invention compounds carbon nanotubes or graphene with magnetic particles at a compounding ratio of 5%-10%, forming a magnetorheological fluid with electromagnetic dual functions. The high conductivity and unique two-dimensional structure of carbon-based materials effectively improve the response speed of the magnetorheological fluid under the action of a magnetic field, shortening the magnetic response time to less than 30 seconds, while achieving the maximum viscosity adjustment capability within 2 seconds, meeting the needs of high dynamic adjustment. Compared with the problems of slow response speed and limited shear stress adjustment range of a single magnetic particle system in the prior art, the present invention has solved the technical problems of large response delay and insufficient adjustment accuracy of magnetorheological fluid, and broadened its application scope in the field of rapid response.

[0065] 4. The present invention optimizes the combination of base liquid and stabilizer, adopts mineral oil, water-based liquid or a mixture thereof as the base liquid, and adds sodium dodecylbenzene sulfonate (SDBS) or polyvinyl pyrrolidone (PVP) as a surfactant, and uses them in a ratio of 0.5%-5%. This technical solution reduces the sedimentation rate of the magnetorheological fluid while improving the anti-shear stratification performance, ensuring the stability of the rheological properties under high temperature, high shear and long-term use. Compared with the problems of particle sedimentation and stratification and rapid performance decay caused by poor matching of the base liquid and the stabilizer in the prior art, the present invention creatively solves the problems of insufficient long-term stability and limited applicable environment of the magnetorheological fluid, and broadens its practical application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a process flow chart for preparing high-performance magnetorheological fluid. DETAILED DESCRIPTION

[0067] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0068] Please see attached Figure 1 :

[0069] Example 1: High stability, low sedimentation magnetorheological fluid

[0070] formula:

[0071] Magnetic particles: 50%, composed of ferrite (Fe3O4), cobalt ferrite (CoFe2O4), nickel ferrite (N i Fe2O4) in a ratio of 1:1:1, with a particle size of 20nm;

[0072] Surface modifier: polyvinyl alcohol (PVA) 6% + polyethyleneimine (PE I) 4%;

[0073] Base fluid: mineral oil 70%;

[0074] Stabilizer: Sodium dodecylbenzene sulfonate (SDBS) 2%.

[0075] Preparation process:

[0076] Synthesis of magnetic particles: The hydrothermal method was used with a reaction temperature of 180°C, a reaction time of 8 hours, and a precursor concentration of 0.5 mol / L to obtain magnetic particles with uniform particle size distribution.

[0077] Surface modification: The magnetic particles were added into a mixed solution containing 8% PVA and 4% PE I, stirred for 60 minutes, left to stand for washing and then dried at low temperature.

[0078] Preparation of base liquid: Mix mineral oil and SDBS and stir at high speed until uniform.

[0079] Uniform dispersion: gradually add the modified particles into the base liquid and use ultrasonic dispersion equipment to treat for 30 minutes to make the particles evenly dispersed.

[0080] Test results:

[0081] Sedimentation performance test: No obvious stratification and sedimentation after standing for 12 months.

[0082] Shear resistance: The attenuation rate of rheological properties under high shear rate conditions is less than 2%.

[0083] Shear stress adjustment range: from 2Pa to 450Pa.

[0084] This embodiment uses ternary composite magnetic particles and a two-component surface modifier to significantly improve the dispersibility and stability of the magnetic particles, and combines mineral oil and SDBS to ensure the anti-sedimentation ability of the magnetorheological fluid. The experimental results show that the magnetorheological fluid is suitable for long-term static or high stability scenarios.

[0085] Example 2: Fast response and enhanced conductivity magnetorheological fluid

[0086] formula:

[0087] Magnetic particles: 45%, composed of ferrite matrix composite carbon nanotubes (CNTs), particle size 15nm;

[0088] Surface modifier: polyvinyl alcohol (PVA) 5% + polyethyleneimine (PE I) 3%;

[0089] Base fluid: mineral oil 50% + deionized water 30%;

[0090] Stabilizer: polyvinylpyrrolidone (PVP) 1.5%;

[0091] Conductive composite material: Graphene 6%.

[0092] Preparation process:

[0093] Synthesis of magnetic particles: The magnetic particles were composited with carbon nanotubes by a solvent thermal method at a reaction temperature of 150° C. for a reaction time of 6 hours to obtain composite particles with a particle size of 15 nm.

[0094] Surface modification: The composite particles were added into a 5% PVA and 3% PE I solution, stirred for 90 minutes, washed and dried.

[0095] Mix the base liquid and stabilizer: Mix mineral oil and deionized water in a ratio of 5:3, add PVP and stir evenly.

[0096] Uniform dispersion: Add the modified particles and graphene into the base liquid and treat with high-speed shear dispersion equipment for 30 minutes.

[0097] Test results:

[0098] Magnetic response speed test: Under 0.5T magnetic field, the magnetic response time is less than 5 seconds.

[0099] Enhanced conductivity: The conductivity of composite graphene is increased by 40%.

[0100] Shear stress adjustment range: 10Pa to 500Pa.

[0101] This embodiment improves the electromagnetic synergy of the magnetorheological fluid by introducing carbon-based conductive materials (graphene and carbon nanotubes), making it excellent in dynamic response speed and conductivity, and is suitable for dynamic control systems and high-speed response equipment. At the same time, due to the smaller particle size, the viscosity response of the system is faster, and compared with Example 1, the applicable scenario focuses more on fast-response equipment.

[0102] Compared with Example 1, the addition of the conductive composite material improves the electromagnetic performance, but the stability is slightly reduced due to the addition of deionized water. Therefore, the magnetorheological fluid is more suitable for short-term dynamic conditions rather than long-term static conditions.

[0103] Example 3: High temperature resistant, long life magnetorheological fluid

[0104] formula:

[0105] Magnetic particles: 55%, particle size 25nm;

[0106] Surface modifier: polyvinyl alcohol (PVA) 5%;

[0107] Base fluid: synthetic oil 70% + water-based liquid (deionized water) 10%;

[0108] Stabilizer: polyvinylpyrrolidone (PVP) 2.5%.

[0109] Preparation process:

[0110] Synthesis of magnetic particles: hydrothermal method, reaction temperature 200 °C, reaction time 10 hours, precursor concentration 0.7 mol / L.

[0111] Surface modification treatment: Add the particles into PVA solution, treat for 30 minutes, wash and dry.

[0112] Preparation of base liquid: Mix synthetic oil and deionized water in a ratio of 7:1, add PVP and stir evenly.

[0113] Uniform dispersion: Add the modified particles into the base liquid, stir at high speed for 15 minutes, and then disperse by ultrasonic for 20 minutes.

[0114] Test results:

[0115] High temperature performance test: Under 200℃ condition, the rheological performance attenuation rate is less than 1.5% after long-term use.

[0116] Anti-sedimentation ability: No obvious sedimentation after standing for 12 months.

[0117] Shear stress adjustment range: 2Pa to 500Pa.

[0118] This embodiment uses high temperature resistant synthetic oil and high efficiency stabilizer (PVP) to make the magnetorheological fluid have excellent high temperature anti-fading performance, suitable for long-term use in harsh environments. Compared with embodiment 1, its high temperature performance is significantly enhanced, but its adaptability to low temperature conditions is relatively weak.

[0119] This embodiment has excellent high temperature tolerance and anti-attenuation capabilities and is suitable for high temperature working conditions. However, since the ratio of synthetic oil to water-based liquid limits the conductivity and dynamic response speed, its applicability is different from that of Example 2.

[0120] Example 4: High-strength shear-resistant magnetorheological fluid

[0121] formula:

[0122] Magnetic particles: 60%, particle size 30nm;

[0123] Surface modifier: polyethyleneimine (PEI) 10%;

[0124] Base fluid: mineral oil 65%;

[0125] Stabilizer: Sodium dodecylbenzene sulfonate (SDBS) 1.5%.

[0126] Preparation process:

[0127] Synthesis of magnetic particles: Solvothermal method was used, reaction temperature was 170°C, reaction time was 8 hours, and precursor concentration was 0.5 mol / L.

[0128] Surface modification: The magnetic particles were added to the PEI solution, stirred for 90 minutes, washed and dried.

[0129] Preparation of base liquid and stabilizer: Mix mineral oil and SDBS and stir until stable.

[0130] Uniform dispersion: Add the modified particles into the base liquid, stir at high speed for 15 minutes, and then disperse by ultrasonic for 30 minutes.

[0131] Test results:

[0132] Shear resistance test: Under high shear conditions, the viscosity retention rate of the magnetorheological fluid reaches 95%.

[0133] Shear stress adjustment range: 20Pa to 500Pa.

[0134] This embodiment is designed for high-intensity working conditions, and adopts large-particle magnetic particles and enhanced modifier PEI, so that the magnetorheological fluid can still maintain excellent viscosity stability at high shear rates, and is suitable for heavy-load industrial equipment.

[0135] Compared with other embodiments, the larger particle size provides a wider shear stress range, but the response speed is slightly reduced due to the higher particle distribution and base fluid viscosity.

[0136] These embodiments are refined from aspects such as stability, dynamic response, high temperature performance and shear resistance, and a magnetorheological fluid design system with clear logic and complementary functions is constructed.

[0137] Comparative experiment:

[0138] Experiment 1: Effect of magnetic particle composition on shear stress adjustment range and magnetic response speed

[0139] Purpose:

[0140] The advantages of the ternary composite magnetic particle system (ferrite, cobalt ferrite, nickel ferrite) used in the present invention are verified to solve the problems of narrow adjustment range and slow magnetic response speed of single magnetic particles in the prior art.

[0141] Technical solution:

[0142] Experimental group (the scheme of the present invention)

[0143] Magnetic particles: ferrite (Fe3O4), cobalt ferrite (CoFe2O4), and nickel ferrite (NiFe2O4) are compounded in a ratio of 1:1:1, and the particle size is controlled to be 20 nm.

[0144] Preparation method: hydrothermal method, temperature 180°C, reaction time 8 hours, precursor concentration 0.5 mol / L.

[0145] Control group 1 (single magnetic particle in the prior art)

[0146] Magnetic particles: ferrite (Fe3O4), particle size 20nm.

[0147] Preparation method: hydrothermal method, temperature 180°C, reaction time 8 hours.

[0148] Control group 2 (existing binary composite particles)

[0149] Magnetic particles: ferrite (Fe3O4) and cobalt ferrite (CoFe2O4) are compounded in a 1:1 ratio, with a particle size of 20 nm.

[0150] Experimental process:

[0151] Magnetic particle synthesis:

[0152] Fe 3+ 、Co 2+ 、N i 2+ The solutions were mixed according to the proportions and the pH was adjusted to 10 by adding NaOH.

[0153] The reaction was carried out at 180°C for 8 hours, and the particle size distribution was measured after washing and drying.

[0154] Surface modification:

[0155] Each group of magnetic particles was modified with 6% polyvinyl alcohol (PVA) and 4% polyethyleneimine (PEI).

[0156] Magnetorheological fluid preparation:

[0157] The modified particles were dispersed in mineral oil at a mass ratio of 50%, and 2% sodium dodecylbenzene sulfonate (SDBS) was added. The particles were stirred at high speed for 10 minutes and then dispersed by ultrasound for 30 minutes.

[0158] test:

[0159] Shear stress range: measured by rheometer under 0.5T magnetic field.

[0160] Magnetic response speed: The time required for the viscosity to stabilize after applying a magnetic field.

[0161] Experimental data

[0162]

[0163]

[0164] The ternary composite system of the present invention achieves rapid magnetic response (within 5 seconds) and a wider shear stress adjustment range (2-500 Pa), far exceeding single or binary composite systems.

[0165] The single magnetic particles in the prior art have weak magnetic properties, limited adjustment range and slow response speed. Although the binary system has been improved, it is not as stable as the ternary system.

[0166] Experiment 2: Effect of surface modifiers on particle dispersibility and stability

[0167] Purpose:

[0168] Verify the advantages of the two-component surface modifier (PVA+PEI) in improving particle dispersibility and anti-sedimentation performance, and solve the problem of insufficient particle stability caused by a single modifier in the existing technology.

[0169] Technical solution:

[0170] Experimental group (the scheme of the present invention)

[0171] Modifier: PVA6%+PE I4%.

[0172] Control group 1 (existing technology single modifier PVA)

[0173] Modifier: PVA 6%.

[0174] Control group 2 (existing technology single modifier PEI)

[0175] Modifier: PE I4%.

[0176] Experimental process:

[0177] Magnetic particle synthesis:

[0178] Preparation of ternary composite magnetic particles (particle size 20 nm).

[0179] Surface modification:

[0180] The magnetic particles are dispersed in different modifier solutions, stirred for 60 minutes, left to stand, washed and dried for later use.

[0181] Magnetorheological fluid preparation:

[0182] The modified particles were added with mineral oil, 2% SDBS, stirred at high speed for 10 minutes and then dispersed by ultrasound for 30 minutes.

[0183] test:

[0184] Dispersibility: Dynamic light scattering was used to test particle size distribution.

[0185] Stability: The sedimentation rate was measured after standing for 12 months.

[0186] Experimental data:

[0187]

[0188] The two-component surface modifier of the present invention synergistically enhances the dispersibility and anti-sedimentation ability of the particles, and the sedimentation rate is reduced to 0.2%.

[0189] A single modifier (PVA or PEI) has limited effect on particle stability and is prone to agglomeration and sedimentation.

[0190] Experiment 3: Effect of base fluid system on high temperature stability

[0191] Purpose

[0192] Verify the viscosity retention and anti-settling performance of the mixed base fluid of synthetic oil and water-based liquid under high temperature conditions to solve the problem of insufficient stability of the existing single base fluid system.

[0193] Technical solution:

[0194] Experimental group (the scheme of the present invention)

[0195] Base fluid: synthetic oil 70% + water-based liquid (deionized water) 10%.

[0196] Control group 1 (single mineral oil in the prior art)

[0197] Base fluid: mineral oil 100%.

[0198] Control group 2 (prior art single water-based liquid)

[0199] Base liquid: deionized water 100%.

[0200] Experimental process:

[0201] Magnetorheological fluid preparation:

[0202] Each group used the same ternary composite magnetic particles and two-component modifier.

[0203] The magnetic particles were added into the base liquid at a mass ratio of 50%, stirred at high speed for 10 minutes and then dispersed by ultrasonic for 30 minutes.

[0204] High temperature performance test:

[0205] The sample was placed in a 200°C environment for 72 hours and the viscosity change was measured.

[0206] After standing for 12 months, observe the sedimentation phenomenon and record the sedimentation rate.

[0207] Experimental data:

[0208]

[0209] The viscosity retention rate of the mixed base liquid system of the present invention is as high as 98% under high temperature conditions, far exceeding that of a single base liquid system, and there is no stratification phenomenon.

[0210] Single mineral oil or water-based liquids have obvious sedimentation problems and cannot meet the requirements of high temperature and long-term use.

[0211] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high performance magnetorheological fluid, characterized in that: The raw material composition includes the following mass percentages: Magnetic particles: 40%-60%, the magnetic particles are composed of ferrite, cobalt ferrite, nickel ferrite or their alloys, the composition ratio of ferrite, cobalt ferrite and nickel ferrite is 1:1:1, and the particle size ranges from 10 to 100 nm; Surface modifier: 1%-10%, the surface modifier is polyvinyl alcohol, polyethyleneimine, polyacrylic acid or a combination thereof, the mass concentration of the polyvinyl alcohol is 10%-20%, and the mass concentration of the polyethyleneimine is 5%-10%; Base fluid: 60%-90%, the base fluid is mineral oil, water-based liquid, synthetic oil or a mixture thereof; Stabilizer: 0.5%-5%, the stabilizer is a surfactant, used to prevent the aggregation and sedimentation of magnetic particles, the surfactant is sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone or a combination thereof.

2. A high performance magnetorheological fluid according to claim 1, characterized in that: The synthesis method of the magnetic particles is a hydrothermal method or a solvothermal method, the reaction temperature is controlled at 120°C to 200°C, the reaction time is 2 hours to 12 hours, the precursor concentration is 0.1 mol / L to 1 mol / L, and the particle size of the magnetic particles is controlled between 10nm-50nm.

3. A high performance magnetorheological fluid according to claim 1, characterized in that: The surface modifier is a combination of polyvinyl alcohol and polyethyleneimine, wherein the mass concentration of polyvinyl alcohol is 10%-20%, the mass concentration of polyethyleneimine is 5%-10%, and the total mass concentration of the surface modifier is 5%-15%.

4. A high performance magnetorheological fluid according to claim 1, characterized in that: The base liquid is mineral oil, water-based liquid, synthetic oil or a mixture thereof, the water-based liquid is deionized water, alcohol solution or saline solution, and the surfactant is sodium dodecylbenzene sulfonate or polyvinyl pyrrolidone.

5. A high performance magnetorheological fluid according to claim 1, characterized in that: The surface of the magnetic particles is coated with a ceramic material, which is SiO2 or TiO2, and the coating ratio is 2%-5%.

6. A high performance magnetorheological fluid according to claim 1, characterized in that: The magnetic particles are compounded with an electrically conductive composite material, the electrically conductive composite material is carbon nanotubes or graphene, and the compounding ratio is 5%-10%.

7. A process for preparing a high-performance magnetorheological fluid according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) synthesizing magnetic particles, wherein the magnetic particles are composed of ferrite, cobalt ferrite or nickel ferrite, synthesized by a hydrothermal method or a solvothermal method, and the particle size is controlled between 10 nm and 50 nm; (2) surface modification treatment, coating the surface of the magnetic particles, wherein the coating material is polyvinyl alcohol or polyethyleneimine, and the mass concentration of the surface modifier is 1%-10%; (3) preparing a base liquid, selecting mineral oil as the base liquid, and adding a stabilizer, wherein the stabilizer is a surfactant, and the concentration of the surfactant is 0.5%-5%; (4) Mixing preparation: adding the surface-modified magnetic particles into the base liquid, and uniformly dispersing them by high-speed stirring or ultrasonic dispersion technology to obtain a magnetorheological fluid.

8. The process for preparing a high-performance magnetorheological fluid according to claim 1, characterized in that: The magnetorheological fluid is used to adjust shear stress within a magnetic field strength range of 0.1T to 1.0T, and the shear stress variation range is 2Pa to 500Pa.

9. The process for preparing a high-performance magnetorheological fluid according to claim 1, characterized in that: The magnetic response time of the magnetorheological fluid is less than 30 seconds, and the viscosity adjustment ability under the action of the magnetic field reaches the maximum response value within 2 seconds.